CEZURA ŚMIERCI W LITERACKIM UJĘCIU ARTHURA SCHNITZLERA (1862-1931) NA PODSTAWIE OPOWIADANIA DER TOD DES JUNGGESELLEN - Łukasik, Krystian (Społeczeństwo, 2026)
Arthur Schnitzler is one of the leading figures of German-language modernist literature. As is widely known, this era was revolutionary in every aspect. Most notably, interpersonal relationships and moral principles changed at that time. Emotional instability, the desire to seize the moment, and an increased focus on the individual led to a moral revaluation. The author himself can also be associated with a certain fascination with dying, death and the psychological ambivalence people exhibit toward these processes. The short story Der Tod des Junggesellen (1912) weaves together themes of social change, secrecy, and infidelity in human relationships around the central motive of death and a post-mortem letter addressed to friends summoned to witness the dying man’s final hour. Death, in this context, becomes an unmistakable occasion for honest confessions – yet these revelations seem less like acts of remorse than calculated gestures of revenge or spite.